Bilateral Traumatic Basal Ganglia Hemorrhage Associated with Diffuse Axonal Injury: A Report on Two New Cases and Review of Existing Literature - Bathla, Girish; Nagpal, Prashant; D'Alessandro, Michael P. (Indian Journal of Neurotrauma, 2016)
Traumatic basal ganglia hemorrhage (TBGH) refers to development of intraparenchymal bleed with in the basal ganglia, internal capsule, or thalamus. Though the reported incidence of TBGH is approximately 3% of all closed-head injuries, bilateral TBGH is much rarer, with only 13 cases reported to date. We present two additional cases of bilateral TBGH posttrauma, along with a review of the existing literature.
Keywords: bilateral basal ganglia hemorrhage; diffuse axonal injury; trauma